KEARIFAN SUFISME DALAM ISLAMISASI JAWA - Purwadi Purwadi (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article shows the wisdom of Sufism on social transformationin Java at the early spread of Islam. Sufism approach tends to emphasizeon self-awareness while accommodating ornamental outer symbols. Thispattern makes the process of being Muslims in Java more peaceful andacceptable for those who already have certain believe and religion (animism,Hinduism and Buddhism).